Axial flow ventricular assist devices in cardiogenic shock complicating acute myocardial infarction. Issue 23 (2nd April 2021) - McGovern, Laurna; Cosgrave, John
Abstract : Cardiogenic shock (CS) remains the leading cause of death in patients hospitalised with acute myocardial infarction with mortality as high as 40%–50% prior to hospital discharge. The failure of inotropic therapy to maintain adequate perfusion and to prevent irreversible end-organ failure has led to attempts to improve outcomes by mechanical circulatory support (MCS) devices. Axial flow ventricular assist devices, namely Impella, are an attractive therapeutic option due to their positive haemodynamic benefits and ease of use. Despite clear beneficial haemodynamic effects, which should significantly impact on the pathophysiology of CS, there are currently no clear data to support their use in the reduction of clinical end points such as cardiac death. This review summarises and critically evaluates the current scientific evidence for the use of axial flow ventricular assist devices and highlights gaps in our understanding. Given such gaps, a consensus multidisciplinary approach, predicated on emphasising timely diagnosis and appropriate use of MCS, is vital to ensure that the right patient is paired with the right device at the right time.